Penerapan Model Pembelajaran Problem Based Learning untuk Menganalisis Keterampilan Pemecahan Masalah Siswa SMP pada Materi Cahaya - Arini Rosa Sinensis; Thoha Firdaus; T Hardila; Nopitasari Nopitasari; N Saiputri (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
The challenge of 21st century education is to prepare human resources who are required to have skills, one of which is problem solving. The Problem Based Learning (PBL) learning model is considered effective in training problem-solving skills because it has constructivist characteristics with science learning. The purpose of this study was to analyze students' problem solving skills in the Light material through PBL learning. The research method used is quantitative with descriptive analysis. The research sample was 22 Tanah Merah Integrated Junior High School students grade IX. The data collection technique used the observation sheet of problem solving skills. The results showed that there was an increase in students' problem solving skills from the first to the third experiment. The increase with the highest percentage was in the third experiment with indicators of problem solving/ investigation by 90.9%. The average data for each problem solving indicator shows that students can understand the problem by 80.78%, collect data by 69.63%, carry out problem solving/investigation by 78.46%, and make conclusions by 66.67%. These results indicate that the Problem Based Learning model can be used as a science learning construction in improving problem solving skills.